Analisis Perbandingan Metode Zmijewski dan Grover dalam Memprediksi Kebangkrutan Bank yang Terdaftar pada BEI Tahun 2015-2019 - Amel Dewi Utari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Bankruptcy is the lowest position in a company because of financial problems. This problem is due to the failure of the company's management efforts to follow up on financial problems. Using Zmijewski and Grover methods, this study chose this method because both methods have three series calculation instruments and the same ROA. Therefore, an early warning signal is needed to anticipate the bankruptcy that occurs. The population in this study includes as many as 42 companies from the banking sector listed on the Indonesia Stock Exchange in 2015-2019. By using the purposive sampling technique, a total sample of 12 banking. The data used is secondary data from the company's annual financial statements. This research was processed with SPSS to obtain the results of significant differences between the Zmijewski model and the Grover model in predicting bankruptcy in banking listed on the Indonesia Stock Exchange from 2015 to 2019.